2014
DOI: 10.1097/ajp.0000000000000005
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Epidural or Intravenous Ketamine Does Not Improve the Effectiveness of Thoracic Epidural Analgesia for Acute and Chronic Pain After Thoracotomy

Abstract: Adding epidural or IV racemic ketamine to TEA after thoracotomy did not lead to any reduction in PPP or allodynia. Epidural administration produced similar plasma ketamine levels to the IV route.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
82
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(84 citation statements)
references
References 58 publications
0
82
1
1
Order By: Relevance
“…One study of 185 participants, in a dose-escalation, double-blind, randomized, placebo-controlled phase III trial, where ketamine or the placebo were delivered subcutaneously over 3 to 5 d, concluded that ketamine does not have a net clinical benefit when used as an adjunct to opioids and standard co-analgesics in cancer pain [81] . A study on patients undergoing thoracotomy suggested that adding epidural or iv racemic ketamine to thoracic epidural analgesia after thoracotomy did not lead to any reduction in persistent post-surgical pain or allodynia [82] . Ketamine could be an alternative choice for pain therapy in patients with chronic pain where standard analgesics, such as opioids, or other treatments are insufficient [83] .…”
Section: Chronic Pain Managementmentioning
confidence: 99%
“…One study of 185 participants, in a dose-escalation, double-blind, randomized, placebo-controlled phase III trial, where ketamine or the placebo were delivered subcutaneously over 3 to 5 d, concluded that ketamine does not have a net clinical benefit when used as an adjunct to opioids and standard co-analgesics in cancer pain [81] . A study on patients undergoing thoracotomy suggested that adding epidural or iv racemic ketamine to thoracic epidural analgesia after thoracotomy did not lead to any reduction in persistent post-surgical pain or allodynia [82] . Ketamine could be an alternative choice for pain therapy in patients with chronic pain where standard analgesics, such as opioids, or other treatments are insufficient [83] .…”
Section: Chronic Pain Managementmentioning
confidence: 99%
“…Various studies have been conducted with pain treatments such as intercostal nerve block, iv-PCA, and ketamine administration (5,7,27,28). However, the optimum method to treat post-thoracotomy pain is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Post-thoracotomy pain is found in 20% to 80 % patients who have undergone thoracotomy using a chest retractor through the intercostal space (1)(2)(3)(4)(5)(6)(7)(8)(9). Epidural analgesia is known to be the gold standard for controlling pain during the perioperative period (10)(11)(12); however, its effectiveness has not been satisfactory after thoracotomy (7,13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Systemic ketamine is reported to be effective to decrease the acute postthoracotomy pain [3236]. Epidural ketamine is also reported to be effective in prevention of acute postthoracotomy pain and development of chronic postthoracotomy pain syndrome [37].…”
Section: Treatmentsmentioning
confidence: 99%